THE ROLE OF CASH HOLDING IN INCREASING FIRM VALUE - Luluk Muhimatul Ifada; Maya Indriastuti; Rustam Hanafi (JRAK, 2020)
This study aims to examine the role of cash holding in mediating the effect of leverage on firm value. The object of this research is 423 manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. The sampling technique used in this research is purposive sampling, with the criteria of manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018, publishing financial reports, and having complete data related to research variables so that a sample of 124 manufacturing companies was obtained. The analysis technique used in this research multiple linear regression analysis and path analysis. The results showed that leverage had a significant negative effect on cash holding and cash holding had a significant positive effect on firm value. Leverage has no significant positive effect on firm value. Cash holding is not able to mediate the effect of leverage on firm value.